From moukoury, bâ and rawiri: where are the essential husbands? (2008)
The entrance of Francophone African women writers into African literary field marks a new era. Kuoh Moukoury’s Rencontres essentielles (1969) considered a ground breaking piece received applause in academic circle when it was published. This paper focuses on the mutation of initially loving and caring husbands of female personae of Kuoh Moukoury, Ba and Rawiri’s novels. The following question is central to this article: “Why did the husbands of the female protagonists of the selected texts turned into unfaithful husbands and why are these women treated as ‘non-being’ like Medea in Euripides," and "What led to the metamorphosis of especially female characters in Ba and Rawiri’s works?” Antonio Gramsci’s theory on subalternity is adopted to analyze the texts and to see the evolution of the female protagonists who engage in struggle to destroy cultural and patriarchal ethos that enslave them.